Pendekatan Saintifik Menggunakan Software Graphmatica untuk Menumbuhkan Kemampuan Komunikasi Matematika - Widiawati Widiawati; Indah Widyaningrum (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2019)
The purpose of this study was to find out the mathematical communication skills of students during the scientific approach was applied using graphmatica software on function graph material in college. This research was an experimental study in the category of one group pretest posttest design involving 30 first semester students of mathematics education study program at STKIP Muhammadiyah Pagaralam. The results showed that students’ mathematical communication skills during the applied scientific approach using graphmatica software on function graph material were classified as very good. This means that the use of graphmatica software through the scientific approach can build students’ mathematical communication skills. Through the learning process based on a scientific approach consisting of observing, quetioning, associating, experimenting, and networking, students’ mathematical communication skills both verbally and in writing are classified as very good. For this reason, these activities have a positive influence on students. Beside building students’ mathematical communication this approach also influence students’ learning outcomes. Better the mathematical communication skills, better the learning outcomes. Therefore, building mathematical communication skills is very important in learning especially in learning through a scientific approach using graphmatica software. The use of graphmatica software can be used in other course such as calculus courses. So, graphmatica software can be used in other course so that it is not limited according to the design of the material to be implemented.